Iowa Birdline update, September 21, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Email for the Iowa Birdline update for September 21, 1992. Highlights of the update include sightings of a Red Phalarope, Yellow Rail and a road-killed Burrowing Owl. Also included are handwritten notes for the next week's update with sightings of as many as 227 raptors counted over a five-day period in Johnson County. The majority of the raptors consisted of Broad-winged Hawks. Epson - sheet feed/flatbed